The Quality of the Recent High-Growth Episode in Sub-Saharan Africa - Martinez, Marcelo (IMF Working Papers; Working Paper ;, 2013)
The paper explores the quality of the recent high-growth episode in sub-Saharan Africa by examining the following two questions: (i) what has been the nature and pattern of SSA growth over the past 15 years and how does it compare with previous episodes? (ii) has this growth had an impact on socially desirable outcomes, for example, improvements in health, education and poverty indicators? To do this, the paper first examines various aspects of the fundamentals of growth in SSA-levels, volatility, sources, et cetera-according to various country analytical groupings. Second, it explores the extent to which the growth has been accompanied by improvements in social indicators. The paper finds that the quality of growth in SSA over the past 15 years has unambiguously improved, although progress in social indicators has been uneven.